Halomonas getboli sp. nov., a halotolerant bacteria isolated from a salt flat. Issue 12 (16th December 2022) - Yoo, Yeonjae; Lee, Hanbyul; Khim, Jong Seong; Xu, Xiaoyue; Kim, Bogun; Choi, In-Geol; Kim, Jae-Jin
Abstract : A novel Gram-stain-negative, rod-shaped, cream-coloured, motile, halotolerant bacterium, designated as YJPS3-2 T, was isolated from saltern sediment of the Yellow sea in Yongyu-do, Republic of Korea. Strain YJPS3-2 T grew at pH 5.0–10.0 (optimum, pH 7.0), 4–40 °C (optimum, 30 °C) and with 1–15% (w/v) NaCl (optimum 3 %). The 16S rRNA gene sequence analysis indicated that strain YJPS3-2 T was closely related to those of Halomonas halophila F5-7 T (98.75 %), Halomonas salina F8-11 T (98.74 %), Halomonas smyrnensis AAD6 T (98.66 %), Halomonas organivorans G-16.1 T (98.34 %), Halomonas koreensis SS20 T (97.98 %) and Halomonas beimenensis NTU-107 T (96.93 %). The average nucleotide identity and digital DNA–DNA hybridization values between YJPS3-2 T and related type strains were 86.9–91.6 % and 32.0–44.8 %. Strain YJPS3-2 T was characterized as having Q-9 as the predominant respiratory quinone and the principal fatty acids (>10 %) were C16 : 0 (31.4 %), C19 : 0 ω 8 c cyclo (16.3 %), C17 : 0 cyclo (11.9 %) and C12 : 0 3-OH (10.4 %). The polar lipids consisted of phosphatidylcholine, diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol. The DNA G+C content of strain YJPS3-2 T is 68.1mol %. Based on the polyphasic taxonomic evidence presented in this study, YJPS3-2 T should be classified as representing a novel species within the genus Halmonas, for which name Halomonas getboli is proposed, with the type strain YJPS3-2 T (= KCTC 92124 T =KACC 22561 T =JCM 35085 T ).